Development of the Dynamic Model of Occupation-Based Practice - Sarah M. Psillas; Wendy B. Stav (Scholarworks @ WMU, 2021)
Background: Occupation-based practice is unique to occupational therapy, supported as effective in the literature, and promotes health and well-being for clients. There is no framework describing what occupation-based practice looks like, making the goal of infusing occupation into practice difficult. This research study aimed to develop a model of occupation-based practice, providing a framework with constructs, facilitators, and barriers for using occupation in practice. Method: A grounded theory study was completed with interviews and a focus group. Charmaz's approach to grounded theory was used to analyze data and allow a model to emerge. Results: The dynamic model of occupation-based practice emerged with four constructs, including actual occupation, meaningful and purposeful value, therapeutic intent, and engaged participation. The model explains the ever-changing process of therapeutic interactions depicting the essence of the interaction along a continuum between a discrete model and occupation-based practice. Conclusion: The model derived from this study offers a framework to operationalize the approach to occupational therapy practice espoused by the profession's leaders and theorists to provide uniquely occupational services. This model can inform the profession at the practice, academic, scholarly, and administrative levels to support enhanced practice, evaluate programs, and study occupation-based practice.